2020
DOI: 10.3390/jcm9051319
|View full text |Cite
|
Sign up to set email alerts
|

Scoring System for Identification of “Survival Advantage” after Successful Percutaneous Coronary Intervention in Patients with Chronic Total Occlusion

Abstract: Background: Percutaneous coronary intervention (PCI) is widely used in patients with chronic total occlusion (CTO), but its benefit in improving long-term outcomes is controversial. We aimed to develop a prediction score for grading “survival advantage” conferred by successful results of CTO-PCI and a scoring system for prediction of the influence of CTO-PCI results on major adverse cardiac and cerebrovascular events (MACCEs). Methods: Follow-up data of 2625 patients who underwent CTO-PCI at 65 Japanese center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…However, only a limited number of SRs conducted these types of analyses, and ideally authors should provide explanations regarding the selection of variables for these analyses. Future SRs should consider planning for groups of importance that may modify the association between successful PCI and patient outcomes, such as diabetes, multivessel disease, more severe disease, previous myocardial infarction, among others [ 59 ]. It is also important for SRs to evaluate publication bias through graphical and statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a limited number of SRs conducted these types of analyses, and ideally authors should provide explanations regarding the selection of variables for these analyses. Future SRs should consider planning for groups of importance that may modify the association between successful PCI and patient outcomes, such as diabetes, multivessel disease, more severe disease, previous myocardial infarction, among others [ 59 ]. It is also important for SRs to evaluate publication bias through graphical and statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, slow flow at the end of CTO PCI procedure is associated with higher MACE according to the report by Wang et al [ 14 ] and as previously mentioned, we can limit these complications by less aggressive balloon/stent dilation after RA and proper selection of burr size and speed. A multicentre study to identify a survival advantage score to predict the outcome after CTO PCI, reported that the association between three variables (multivessel disease, Canadian cardiovascular society (CCS) score ≥2, and previous MI) in CTO patients predict poor long-term outcome after CTO revascularisation [ 23 ]. In our CTO cohort, multivessel disease was present in 68.8% and about 58.7% had CCS ≥ 2, and 21.3% reported previous MI.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, we should keep in mind that our goal is not to focus on the 'blocked coronary arteries', but to improve anginal symptoms and clinical outcomes in patients with stable ischemic heart disease. In addition to AUC, scoring tools that predict long-term adverse cardiac events 14 or 'survival advantage' 15 after successful CTO procedures can also be a valid instrument for clinical decisionmaking. Careful patient selection and optimizing medical therapy prior to the procedure remain the key components in managing CTO patients.…”
Section: Article P ????mentioning
confidence: 99%